KEMAMPUAN VO2 MAX DAN KEMAMPUAN PEMULIHAN ATLET PENCAK SILAT - SUTISNA, ROMI; Imanudin, Iman (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2018)
This study discusses the relationship of vo2 max capability and the ability of martial arts athletes recovery, the instrument used in this study by using balke test to measure vo2 max and using polar to calculate the pulse. The purpose of this study is to determine and explain whether there is a relationship between the ability of vo2 max and the ability of the athletes recovery pencak silat In this study the researchers chose purposive sampling as the appropriate technique for sampling which researchers took the selected people according to the specific characteristics possessed by the sample that as many as 10 men athletes based on research needs. Research instruments used are data analysis. This research is located in Bandung, West Java precisely at the stadium of Universitas Pendidikan Indonesia, The result states that VO2 Max from the lowest to the highest is 35.6-47.5 and the recovery pulse from the lowest to the highest is 115-159. The results of data processing showed the following discovery: "There is no significant relationship between VO2 Max and the recovery ability of the athlete of pencaksilat".  Kata kunci : Vo2 Max, pencak silat recovery